Socio-Cultural Determinant of Girl Child Education in Cross River State - Eyong, Victoria Amiokama (Kashere Journal of Politics and International Relations, 2024)
Worldwide attention is focused on actualizing the Sustainable Development Goals (SDGs) by 2030. Beyond policies and laws establishing universal basic education, the implementation of UBE's laudable objectives and overcoming the various challenges facing it within the school system are the dominant factors for the attainment of sustainable development goals, most especially SDG 4 and SDG 5. But the worrisome nature of the problem of gender disparity internationally has to be dealt with, so as not to derail that dream. It has been noted that one of the challenges in basic education in Africa remains the disproportionate balance in gender representation in school enrollment. In Nigeria, since the advent of UBE, there has been a noticeable increase in school enrolment, the first step in access to education. Education, a fundamental right of every child and crucial for societal transformation, has seen a rise in female enrollment. Yet, existing studies lack clarity on the cultural factors driving this change. This research aims to explore how parents' cultural and religious beliefs influence girl-child education in Cross River State, involving 7,500 respondents with a sample size of 347, determined using Krejcie and Morgan. Data collection utilized a self-structured questionnaire, and analysis employed descriptive statistics like frequency count and mean. The findings suggest that parents' religious convictions impact the girl child's education, and cultural ideas also play a role.